Sanitation in Fish Curing Yards of Tuticorin, Tamil Nadu - G., Sugumar; T., Jawahar Abraham; P., Jeyachandran (Fishery Technology, 2025)
The method of preparation of cured fish and the sanitary conditions prevailing in the fish curing yards of Tuticorin region were studied. The water used for washing and brine preparation did not conform to the BIS standards and had high counts of viable bacteria, coliforms and fungi. Relatively high counts of viable organisms, coliforms and fungi in worker's hand, soil and curing tanks resulted in poor microbial quality of the cured fish. A lack of awareness of the importance of hygiene and sanitation among the processors and workers was observed during the survey.